2013
DOI: 10.1177/0748233713475516
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to lambda-cyhalothrin, a synthetic pyrethroid, increases reactive oxygen species production and induces genotoxicity in rat peripheral blood

Abstract: Lambda-cyhalothrin (LTC) is a synthetic pyrethroid with a broad spectrum of insecticidal and acaricidal activities used to control a wide range of insect pests in a variety of applications. However, there is little known about its adverse effects, in particular those related to its genotoxicity in humans. To elucidate the genotoxicity mechanisms of LTC, the micronuclei (MN) frequencies, the levels of reactive oxygen species (ROS), erythrocyte osmotic fragility, nitrite (NO) formation, protein carbonyl (PCO) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…The biomarker malondialdehyde (MDA) is a common measure of oxidative stress in honey bees, other insects, and vertebrate systems21222324. MDA is the main organic compound produced from lipid peroxidation of polyunsaturated fatty acids in cellular membranes25.…”
mentioning
confidence: 99%
“…The biomarker malondialdehyde (MDA) is a common measure of oxidative stress in honey bees, other insects, and vertebrate systems21222324. MDA is the main organic compound produced from lipid peroxidation of polyunsaturated fatty acids in cellular membranes25.…”
mentioning
confidence: 99%
“…Although cyhalothrin has relatively low mammalian toxicity, there is still caution with regard to human exposure 8 11 . A number of studies have demonstrated that large dose exposures in mammals may cause significant toxicity and health effects, including neurotoxicity 12 , genotoxicity 13 14 , cytotoxicity 14 15 , and endocrine disruption which can damage mammalian reproduction 16 17 18 . Furthermore, chronic exposure to cyhalothrin even low level exposures may be associated with an elevated risk of mutagenicity 19 , carcinogenicity 20 , as well as childhood leukemia 21 .…”
mentioning
confidence: 99%
“…The oxidative damage could be resulted in cytotoxicity and immune alterations. Several previous reports recorded the generation of ROS, impairment of antioxidant enzyme activities and increased MDA and nitric oxide levels after exposure to LCT [21,23,[52][53][54][55][56]. It is possible that one scenario or more have contributed to the immunotoxic effects induced by LCT.…”
Section: Discussionmentioning
confidence: 96%